2005
DOI: 10.1074/jbc.m505373200
|View full text |Cite
|
Sign up to set email alerts
|

Increased Production of Functional Recombinant Human Clotting Factor IX by Baby Hamster Kidney Cells Engineered to Overexpress VKORC1, the Vitamin K 2,3-Epoxide-reducing Enzyme of the Vitamin K Cycle

Abstract: Some recombinant vitamin K-dependent blood coagulation factors (factors VII, IX, and protein C) have become valuable pharmaceuticals in the treatment of bleeding complications and sepsis. Because of their vitamin K-dependent post-translational modification, their synthesis by eukaryotic cells is essential. The eukaryotic cell harbors a vitamin K-dependent ␥-carboxylation system that converts the proteins to ␥-carboxyglutamic acid-containing proteins. However, the system in eukaryotic cells has limited capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
50
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 22 publications
10
50
1
2
Order By: Relevance
“…While our paper was under review, Wajih et al reported that factor IX expression in baby hamster kidney (BHK) cells could also be helped by coexpressing VKOR. 21 Both this work and that of Hallgren et al 22 and Rehemtulla et al 13 report that GGCX expression actually decreases the amount of functional, carboxylated, vitamin Kdependent protein secreted from the cells. In fact, we recovered slightly more factor X from the cell line overexpressing GGCX than from any of the other cell lines.…”
Section: Discussionmentioning
confidence: 79%
“…While our paper was under review, Wajih et al reported that factor IX expression in baby hamster kidney (BHK) cells could also be helped by coexpressing VKOR. 21 Both this work and that of Hallgren et al 22 and Rehemtulla et al 13 report that GGCX expression actually decreases the amount of functional, carboxylated, vitamin Kdependent protein secreted from the cells. In fact, we recovered slightly more factor X from the cell line overexpressing GGCX than from any of the other cell lines.…”
Section: Discussionmentioning
confidence: 79%
“…Also unknown is whether other cell lines contain similar amounts of this protein, which could impact the ability of r-VKORC1 to increase carboxylation in these lines. Two recent papers (35,36), which examined the effect of r-VKORC1 on VKD proteins secreted from BHK or 293 cells, also reported only 2-3-fold increases in the extent of carboxylated, secreted protein. Our determinations of the rates of in vitro and in vivo carboxylation suggest the possibility that the redox protein is critical to efficiency of carboxylation and that larger increases in carboxylation may not be possible until it is identified and coexpressed with VKORC1.…”
Section: Discussionmentioning
confidence: 99%
“…22 Consequently, VKD factor association with carboxylase results in more efficient vitamin K utilization, which is significant because the availability of KH 2 appears to regulate carboxylation. [23][24][25][26] In the absence of VKD substrate binding, KH 2 epoxidation to KO does not occur, 27 and this regulation prevents the unfettered formation of highly reactive and undesirable vitamin K intermediates. At present, the residues that make up the carboxylase active site to facilitate the reaction are largely unknown, due in part to the lack of a crystal structure or homology with other proteins that might indicate functional residues.…”
Section: Introductionmentioning
confidence: 99%
“…22 Consequently, VKD factor association with carboxylase results in more efficient vitamin K utilization, which is significant because the availability of KH 2 appears to regulate carboxylation. [23][24][25][26] In the absence of VKD substrate binding, KH 2 epoxidation to KO does not occur, 27 and this regulation prevents the unfettered formation of highly reactive and undesirable An Inside Blood analysis of this article appears at the front of this issue.Reprints: Jean-Philippe Rosa, Laboratory of Hemostasis and Thrombosis, U689 Institut National de la Santé Et de la Recherche Mé dicale, Hô pital Lariboisiè re, 41 boulevard de la Chapelle, 75475 Paris Cedex 10, France; e-mail: rosa@larib.inserm.fr.The publication costs of this article were defrayed in part by page charge payment. Therefore, and solely to indicate this fact, this article is hereby marked ''advertisement'' in accordance with 18 U.S.C.…”
mentioning
confidence: 99%